A High-Light Sensitivity Optical Neural Silencer: Development and Application to Optogenetic Control of Non-Human Primate Cortex - Han, Xue; Chow, Brian Y.; Zhou, Huihui; Klapoetke, Nathan C.; Chuong, Amy; Rajimehr, Reza; Yang, Aimei; Baratta, Michael V.; Winkle, Jonathan; Desimone, Robert; Boyden, Edward S. (Frontiers in Systems Neuroscience, 2011)
Technologies for silencing the electrical activity of genetically targeted neurons in the brain are important for assessing the contribution of specific cell types and pathways toward behaviors and pathologies. Recently we found that archaerhodopsin-3 from Halorubrum sodomense (Arch), a light-driven outward proton pump, when genetically expressed in neurons, enables them to be powerfully, transiently, and repeatedly silenced in response to pulses of light. Because of the impressive characteristics of Arch, we explored the optogenetic utility of opsins with high sequence homology to Arch, from archaea of the Halorubrum genus. We found that the archaerhodopsin from Halorubrum strain TP009, which we named ArchT, could mediate photocurrents of similar maximum amplitude to those of Arch (∼900 pA in vitro), but with a >3-fold improvement in light sensitivity over Arch, most notably in the optogenetic range of 1–10 mW/mm2, equating to >2× increase in brain tissue volume addressed by a typical single optical fiber. Upon expression in mouse or rhesus macaque cortical neurons, ArchT expressed well on neuronal membranes, including excellent trafficking for long distances down neuronal axons. The high light sensitivity prompted us to explore ArchT use in the cortex of the rhesus macaque. Optical perturbation of ArchT-expressing neurons in the brain of an awake rhesus macaque resulted in a rapid and complete (∼100%) silencing of most recorded cells, with suppressed cells achieving a median firing rate of 0 spikes/s upon illumination. A small population of neurons showed increased firing rates at long latencies following the onset of light stimulation, suggesting the existence of a mechanism of network-level neural activity balancing. The powerful net suppression of activity suggests that ArchT silencing technology might be of great use not only in the causal analysis of neural circuits, but may have therapeutic applications.